Parasitism of Entedon costalis (Hymenoptera: Eulophidae) in Glocianus punctiger (Coleoptera: Curculionidae): an example of intentional discovery of the parasitoid-host association - Gumovsky, Alex V. (Zootaxa, 2008)
The biology and morphology of early larval instars of Entedon costalis Dalman (Hymenoptera: Eulophidae), are described in detail for the first time. The parasitoid-host association of E. costalis was revealed as a result of selection of candidate host based on combination of assumptions based on biology of related species and field surveys. E. costalis proved to be an egg-larval parasitoid of the weevil Glocianus punctiger (Gyllenhal), which is associated with dandelion (Taraxacum officinale G.H. Weber ex Wiggers). Parasitism rate of G. punctiger by E. costalis was 25% in the model patch which was sampled in May, where infestation of dandelion inflorescence by G. punctiger was 27%. The female of E. costalis lays her egg into the host egg, but the first instar larva hatches within the first instar host. Larvae of G. punctiger start their feeding as internal flower-stalk borers, continue as seed-eaters in flowerheads, and then pupate underground when matured coincident with seed dispersal (generally in the end of May). Parasitized and unparasitized mature larvae of G. punctiger pupate underground, in earthen cells, where the parasitoid larvae finally consume their hosts and pupate 2–3 days thereafter. Adults of E. costalis emerge the following spring (about mid April), as dandelions being flowering. The morphology of immature stages and behaviour of adults is described. Various peculiarities of parasitoidhost relationships superparasitism, siblicide, host immune response are described and discussed. DNA sequences of the nuclear 28S D2 rDNA gene were obtained for E. costalis.